Bulgarian Chamber of Commerce and Industry. Traditions, Achievements, Contemporary Challenges (1895-2010) - Veleva, Lilyana (Research Papers, 2011)
The Bulgarian Chamber of Commerce and Industry (BCCI) is one of the oldest economic institutions in Bulgaria. Since its establishment in the end of 19th century to date it has passed through different phases consecutively undergoing a change of status, name and internal structure under the influence of the internal political and economic processes in the country. Over the decades, regardless of the organizational transformations BCCI has preserved its institutional identity. It has kept and upheld its role of an important factor in economic life by binding its overall activity that is carried out on a regional, national and international level to the interests of Bulgarian manufacturers, traders and entrepreneurs. The chamber is a reliable economic and informational center, a large-scale professional and educational factor, a good sector organizer. Along with this as a non-partisan institution BCCI remains an effective partner of central and local authorities in the field of economic legislation, in development of anti-crisis programs, in the field of European integration.